The New Issue Puzzle: IPO Pricing in the Hot and Cold Markets in India - Agarwal, Shreya (2006)
This dissertation examines the strong cycles in the no. of IPOs that have existed in the Indian IPO markets since 1991 and the level of underpricing that has been observed during such cycles. It even tries to establish a reason behind the hot and cold IPO markets observed in India. It concentrates on two key variables, namely, IPO volume and initial returns and analyses their nature and interrelation during hot (1995-1996) and cold (2004-2005) periods. At the aggregate level the, IPO volume is predictably related to past IPO volume and initial returns are related to past initial returns for the period of 1990-2006. To understand these patterns I use firm level data from 1990-2004 to model initial returns and IPO volume. The results show that the series of IPO volume and initial returns are dependent on their past values which shows a firm's decision to go public over the last decade depended on the number of other companies that were getting listed over the previous months and the relative underpricing. There was a strong negative relationship between the given level of underpricing and the IPO volume in both hot and cold markets. It also establishes that the hot and cold periods in India were a result of the regulatory changes in the economy.